International Survey to Evaluate Current Options for Subcutaneous Injection of Methotrexate (MTX) and a New Button-Free MTX Autoinjector - Müller-Ladner U; Edwards CJ; Erkens A (Patient Preference and Adherence, 2024)
Ulf Müller-Ladner,1 Christopher J Edwards,2 Andreas Erkens3 1Department of Rheumatology and Clinical Immunology, Justus-Liebig-University Giessen, Campus Kerckhoff, Bad Nauheim, Germany; 2Musculoskeletal Research Unit, NIHR Southampton Clinical Research Facility, University Hospital Southampton, Southampton, UK; 3Aurum Research GmbH, Lauf a.d., Pegnitz, GermanyCorrespondence: Ulf Müller-Ladner, Department of Rheumatology and Clinical Immunology, Justus-Liebig-University Giessen, Benekestrasse 2-8, D-61231 Bad Nauheim, Germany, Fax +49 6032-996 2104, Email u.mueller-ladner@kerckhoff-klinik.dePurpose: Prefilled syringes (PFS) and various types of pens are available for subcutaneous injection of methotrexate (MTX) in patients with rheumatoid arthritis or moderate to severe psoriasis. A new MTX pen with modernized button-free autoinjection technology was developed as a successor to a button-activated pen (metoject®/metex® PEN). To assess the needs of users and the relevance of features of the new MTX autoinjector an international online survey was performed.Methods: A structured questionnaire was distributed to physicians, nurses and patients in Germany, France, and the United Kingdom. Participants received illustrations and information about features of the new MTX autoinjector.Results: In total, 189 rheumatologists, 111 dermatologists, 90 nurses, and 180 patients answered the questions. Specific reasons for a preference for the use of MTX pens over PFS could predominantly be assigned to the categories “dosing/administration” and “ease of use”. The first impression of the new MTX autoinjector was positive in 82% of physicians, 87% of nurses, and 76% of patients, respectively. The four most important features of the new MTX autoinjector were 2-step autoinjector mechanism (receiving a mean 14.1 to 18.1 chips of a total of 100 chips), small injection volume (9.7 to 11.7 chips), 10 different doses for dose flexibility (8.0 to 13.2 chips), and short injection time below 5 seconds (8.5 to 11.1 chips).Conclusion: Arguments for the use of MTX pens as opposed to PFS predominantly refer to dosing/administration and ease of use. The new button-free MTX autoinjector combines a number of advantageous features identified by the international survey.Plain Language Summary: Subcutaneous injection of methotrexate (MTX) is an option to treat patients with specific inflammatory diseases. A new MTX autoinjector with button-free activation of the injection and no need to build a skin fold was developed to address some of the reasons for non-adherence. The importance of specific needs of users as well as the relevance of features of the new MTX autoinjector are unknown. Therefore, a structured questionnaire was distributed to physicians, nurses and patients in Germany, France, and the United Kingdom. Illustrations and information about features of the new MTX autoinjector were distributed to the participants. The results of the study show that arguments for the use of MTX pens as opposed to prefilled syringes predominantly affect the categories dosing/administration and ease of use followed by safety/side effects. In addition, the study identified four main advantageous features of the new MTX autoinjector, ie simplicity due to the 2-step button-free autoinjector mechanism, the small injection volume, 10 different doses for dose flexibility, and the short injection time below 5 seconds.Keywords: autoinjector, methotrexate, pen, psoriasis, rheumatoid arthritis, syringe